2012
DOI: 10.1080/11250003.2011.642899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alloxan on ultrastructural and hormonal changes of the endocrine pancreas with hormonal profiles of adrenal gland and their influence on carbohydrate metabolism in soft-shelled turtles,Lissemys punctata punctataBonnoterre

Abstract: Alloxan action on B-and non-B-cells of the endocrine pancreas, adrenal gland and their influence on carbohydrate metabolism are not clearly understood in chelonians. Earlier findings were inconsistent and inexhaustive. These issues were investigated from cytological, ultrastructural, immunocytochemical (B cells) and hormonal (insulin) standpoints in soft-shelled turtles. Alloxan treatment (200 mg/kg body wt on alternate day for 6 days) significantly increased population of necrotic B-cells (87%) with decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In our earlier works we have shown that streptozotocin, like alloxan, also has a diabetogenic effect in soft-shelled turtles. Furthermore, streptozotocin, at least in the same dose and duration, is more potent than alloxan in causing diabetogenic effect in Lissemys turtles, because B-cell necrosis followed by depletion of serum insulin level and hyperglycemia were higher in streptozotocin than alloxan recipients in turtles (Sarkar 2008;Sarkar et al 2012). Moreover, recovery of the diabetogenic effect of SZ from necrosis of B-cells was faster in streptozotocin than alloxan recipients, because the regeneration of new B-cells with consequent rise in insulin level and hypoglycemia occurred in shorter time (14 days) in streptozotocin recipients than alloxan in turtles.…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier works we have shown that streptozotocin, like alloxan, also has a diabetogenic effect in soft-shelled turtles. Furthermore, streptozotocin, at least in the same dose and duration, is more potent than alloxan in causing diabetogenic effect in Lissemys turtles, because B-cell necrosis followed by depletion of serum insulin level and hyperglycemia were higher in streptozotocin than alloxan recipients in turtles (Sarkar 2008;Sarkar et al 2012). Moreover, recovery of the diabetogenic effect of SZ from necrosis of B-cells was faster in streptozotocin than alloxan recipients, because the regeneration of new B-cells with consequent rise in insulin level and hypoglycemia occurred in shorter time (14 days) in streptozotocin recipients than alloxan in turtles.…”
Section: Discussionmentioning
confidence: 99%